Assessing The Role of Executive Procedures in Shaping Sharī’ah Governance Commitments in Saudi Banks - Bashir, Mohamed Sharif; Muslichah, Muslichah; Babiker, Abdo Aglan (Journal of Ecohumanism, 2024)
This paper investigates the relationship between governance dimensions and the level of commitments to Sharī’ah (Islamic law) governance framework within Saudi banks. To understand the intricacies of governance dimensions in shaping Sharī’ah governance practices in depth, this paper also examines the mediating role of executive procedures. Structural equation modeling is used to test the hypotheses regarding the relationship between studied variables. The findings underscore the role of executive procedures, disclosure and transparency in fostering commitments to Sharī’ah governance framework, with both constructs exhibiting substantial direct effects on Sharī’ah governance commitment level. Additionally, the study underscores the importance of monitoring, auditing, and accountability as crucial determinants of governance in banks, highlighting the importance of robust oversight mechanisms in ensuring adherence to Sharī’ah principles. Meanwhile, organisational structure exhibited a minor decrease in its direct effect on commitment to Sharī’ah governance. The findings of this paper can guide the strategic decision-making process for promoting ethical and sustainable Sharī’ah governance practices in Saudi banks. It also fills the existing gap in literature regarding the relationship between the dimensions of governance and the obligations of Sharī’ah governance framework in Saudi banks.